SYNTHESIS AND STRUCTURAL ANALYSIS OF A Cu(II) COMPLEX WITH PYRIDOXAL S-METHYLISOTHIOSEMICARBAZONE (PLITSC) LIGAND - Ivković, S.; Jevtović, V. (Journal of Engineering & Processing Management, 2010)
Reaction between a warm water mixture of pyridoxal hydrochloride (PL.HCl), and Smethyilisothiosemicarbazidehydroiodide (SMeTSC.HI) in the presence of Na2CO3 .10 H O, we got pyridoxal S-methylisothiosemicarbazone (PLITSC; H2L). Ligand with appropriate Cu salt is coordinated, to give next complex: dark-brown, penta coordinated, square-pyramidal structure, mono(ligand)complex Cu(II) formula, [Cu(PLITSC)Br(CH3OH)]Br.In this work is given synthesis and structure of the complex with Schiff-based ligand.